Modelling the impacts of intensifying forest management on carbon budget across a long latitudinal gradient in Europe - Akujärvi, Anu; Shvidenko, Anatoly; Pietsch, Stephan A (Environmental research letters, 2019)
Global wood demand is projected to increase with accompanying intensification in forest management practices. There are concerns that intensive management practices such as whole-tree harvest (WTH) and shortened rotation lengths could risk the long-term productivity and carbon sink capacity of forest ecosystems. The historical (1915-2005) and future (2005-2095) development of five Scots pine (Pinus sylvestris) and five Norway spruce (Picea abies) stands were simulated across a long latitudinal gradient in Europe. The responses of above- and belowground carbon and nutrient cycles to changing forest management and climate were simulated using a biogeochemical ecosystem model and a dynamic litter and soil carbon model. The uncertainty deriving from the inter-annual climate variability was quantified by Monte Carlo simulations. The biogeochemical model estimated the historical stand development similarly to measurement-based estimates derived from growth and yield tables, supporting the validity of the modelling framework. Stand productivity increased drastically in 2005-2095 as a result of climate change. The litter and soil carbon and nitrogen stocks decreased as a result of WTH while its effect on the biomass carbon stock was positive. This indicates that the microbial controls of post-harvest on stand productivity require further research. Shortened rotation length reduced the carbon stock of biomass more than that of litter and soil. The response of the litter and soil carbon stock to forest management was very similar irrelevant of the model used demonstrating the pattern to be robust. Forest management dominated over the impacts of climate change in the short term.